Understanding: Definition and Mechanisms - Shadrikov V.D. (Культурно-историческая психология, 2020)
The article defines understanding as a fact of our mental life. It reviews how understanding is reflected in language, in philosophical literature, in theology. A significant amount of research in the field of psychology is devoted to the problem of understanding, however, the process is obviously under-explored in terms of the mechanisms of understanding in teaching/learning. The following questions are raised: When did the problem of understanding arise? What are the mechanisms of understanding? The paper identifies three factors of understanding-misunderstanding: the connection of understanding with thought producing; the alienation of personal meaning of knowledge when it transforms into meaning; individual models of the child’s world which begin to shape before language is acquired and continue to develop in everyday concepts. The paper attempts to give answers to the questions from the perspective of the cultural-historical approach. Basing on the proposed ideas about the mechanisms of understanding-misunderstanding, it discusses the ways of achieving understanding in the educational process. It is argued that understanding is always concrete as it refers to a particular student, particular topic of the lesson and is closely related to motivation.